Angry Bird's Revenge: Hepatic Abscesses Secondary to Colonic Perforation - Gholamreza Sivandzadeh; Alimohammad Banazadeh; Amir Anushiravani (Acta Medica Iranica, 2018)
Foreign bodies are commonly ingested and usually pass through the gastrointestinal tract, but in less than 1% complications can be seen. We aimed to report a very rare case of multiple hepatic abscesses caused by perforation of the sigmoid colon due to a chicken bone. An 82-year-old man presented with a 5-day history of abdominal pain, fever, and coffee ground vomiting. He was febrile and tachycardic and had a mild localized abdominal tenderness in the left lower quadrant. Laboratory findings revealed a lymphocyte dominant leukocytosis with an elevated erythrocyte sedimentation rate. Multiple abscesses were shown in the right lobe of the liver in abdominal computed tomography. Colonoscopy showed a chicken bone perforating both walls of the sigmoid colon. He received broad-spectrum antibiotics and underwent surgery for a complete recovery. Chronic lymphocytic leukemia was diagnosed by flow cytometry phenotyping. Mortality and morbidity of hepatic sepsis caused by foreign body-induced colon perforation depend on a rapid diagnosis.  We presented a very rare condition that should always be kept in mind when dealing with a case of liver abscess and even while confronting septic shock with an unknown origin.